Condor's Egg - London, Jonathan (San Francisco : Chronic Books, 1994)
The last two California Condors living in the wild hatch an egg.
Keywords: California condor-Juvenile fiction; California condor-Fiction; Condors - Fiction; Rare birds-Fiction; Endangered species-Fiction